Conceptual Framework for the Development of KAFA Courseware - Azilawati, Rozaimee; Wan Malini, Wan Isa; Suhailan, Safei; Fakhrul Anwar, Zainol; Fadhilah, Ahmad (2011)
The use of multimedia courseware in education has been on the increase due to the growth of technologies and Multimedia Super Corridor (MSC). Courseware is one of the approaches that can be used in teaching and learning processes so that it becomes more effective and interesting. This paper discusses a conceptual framework used in the development and innovation of KAFA courseware. The framework consists of multimedia elements and learning theories: and special features of the courseware that includes interactivity, contents updates and learning activities.